Alopecia in patients with COVID-19: A systematic review and meta-analysisCapsule Summary - Betty Nguyen, BS; Antonella Tosti, MD (Elsevier, 2022)
Background: COVID-19 is associated with androgenetic alopecia (AGA), telogen effluvium (TE), and alopecia areata (AA). No studies have analyzed the aggregate data to date. Objective: We conducted a systematic review to characterize the types, incidence, timing, and clinical outcomes of COVID-19-associated alopecia. Methods: We searched PubMed/MEDLINE, Scopus, and Embase for articles published between November 2019 and August 2021 using the key words "alopecia" or "hair" and COVID-19-related search terms, identifying 41 original articles describing patients with alopecia and COVID-19. Results: The current review included 1826 patients with alopecia and COVID-19 (mean age, 54.5 years; 54.3% male). The most common types of alopecia identified were AGA (30.7%, 86.4% male), TE (19.8%, 19.3% male), and AA (7.8%, 40.0% male). AGA preceded COVID-19 symptoms. TE was usually newly triggered by COVID-19 (93.6%). AA usually occurred in patients with preexisting disease (95.1%). Limitations: Definitions of COVID-19 onset varied. Studies differed in methodology and were susceptible to reporting and sampling bias. Studies with large sample sizes may exert a disproportionate influence on data. Conclusion: AGA may be a risk factor for severe COVID-19, whereas TE presents as a sequela of COVID-19. AA generally occurs as a relapse in patients with preexisting alopecia.